2005
DOI: 10.1590/s1415-47572005000100020
|View full text |Cite
|
Sign up to set email alerts
|

Use of the TSPY gene for sexing cattle

Abstract: The Y-encoded, testis-specific protein (TSPY) is a Y-specific gene. The copy numbers of TSPY range from 20 to 60 in men and up to 200 in bulls. In this study, we examined the possibility of using the TSPY gene to sex cattle. DNA from blood samples of 100 Nelore cattle (50 males and 50 females) from the Nelore Cattle Breeding Program (PMGRN) was screened for TSPY by PCR using TSPY-specific primers. The assay was highly specific since all male samples were TSPY-positive and all female samples were negative. Posi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0
2

Year Published

2011
2011
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 17 publications
0
14
0
2
Order By: Relevance
“…In a previous study, we reported that PCR using primers derived from a TSPY sequence allows the detection of the Y chromosome in male animals (Nelore cattle) even at low DNA concentrations. These preliminary results showed the potential of this gene as a male-specific marker (Lemos et al, 2005).…”
Section: Discussionmentioning
confidence: 58%
See 3 more Smart Citations
“…In a previous study, we reported that PCR using primers derived from a TSPY sequence allows the detection of the Y chromosome in male animals (Nelore cattle) even at low DNA concentrations. These preliminary results showed the potential of this gene as a male-specific marker (Lemos et al, 2005).…”
Section: Discussionmentioning
confidence: 58%
“…The application of polymerase chain reaction (PCR) for the analysis of a single cell presents a challenge since limited DNA is available in one single diploid cell, and this can lead to a reduction in amplification efficiency. Lemos et al (2005) described a study on the TSPY (testis-specific protein Y-encoded) gene as a male-specific marker for cattle sexing in very low DNA concentrations. The TSPY gene is advantageous compared to other markers because it is a Y-specific gene of multiple copies both in human and bovine genomes.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Por otro lado, la detección del sexo a partir de una muestra de ADN mediante PCR puede ser realizada usando primers específicos de distintos genes como el SRY, TSPY1, y otros. Dado que el gen TSPY1 es multicopia, es decir, presenta varias copias en bajas concentraciones de ADN, resulta más útil y eficiente como marcador masculino a diferencia de otros genes como el SRY que es de 1 sola copia (Lemos et al, 2005).…”
Section: Montano Vizcarra D Y Colunclassified